Strategic business partner : aligning people strategies with business goals - Robinson, Dana Gaines, 1944-; Robinson, James C., 1930- (Berrett-Koehler, 2005)
This is a practical resource with case examples, exercises and tools ready to use by HR, OD, and learning professionals who aspire to become strategic business partners in their organizations.